Structural characterizarion of extensive farms in Andalusian dehesas - García, A.; Perea, J.; Acero, R.; Angón, E. (Arch. Zoot, 2010)
Three types of livestock farming systems are identified in Andalusian dehesas using multivariate analysis. One of two conservationist systems, both applying sustainable management criteria, was detected in most of farms: dehesa farming system (49% of farms): small extensive cattle and sheep farms, which adapt stocking rates to the availability of the land's natural resources, and occasional use of strategic food supplementation; mountain farming system (21%) also relative to small farms, with mainly small ruminants and limited use of technology. The third system was a yield targeted system (30%), corresponding mainly to large cattle farms, with greater use of technology and high levels of food supplementation caused by stocking rates that exceed the land's carrying capacity. Typology defined can be used as starting point to base technical and economic characterization of farming systems taking into consideration their current and future viability
Keywords: Factorial analysis; Farm typology; Livestock farming systems

Gross output and livestock sales modelling in Spanish extensive farms using PLSR - Gaspar, Paula (107th EAAE Seminar "Modelling of Agricultural and Rural Development Policies". Sevilla, Spain, January 29 th -February 1st, 2008, 2008)
The aim of this paper is to model some production variables in extensive livestock farms located in the dehesa ecosystem. We intend to use not only purely economic variables in the construction of the model, but also structural variables in order to identify the characteristics of the farms that have the higher influence. Another objective is to be able to predict these variables at the farm level, using structural variables that are easy to measure. The data used in this work were obtained from a questionnaire survey to the holders/managers of a sample of 69 dehesa farms in Extremadura (SW Spain). The statistical methodology used for the construction of the model was Partial Least Square Regression (PLSR). It can be concluded that the variables relative to farm intensification, to labour and especially to Iberian pig breeding, are those that take part mainly in the model.
The following values have no corresponding Zotero field: periodical: 107th EAAE Seminar "Modelling of Agricultural and Rural Development Policies". Sevilla, Spain, January 29 th -February 1st, 2008
Keywords: Dehesa; gross output; Livestock farming systems; partial least square regression

Gross output and livestock sales modelling in Spanish extensive farms using PLSR - Gaspar, Paula (107th EAAE Seminar "Modelling of Agricultural and Rural Development Policies". Sevilla, Spain, January 29 th -February 1st, 2008, 2008)
The aim of this paper is to model some production variables in extensive livestock farms located in the dehesa ecosystem. We intend to use not only purely economic variables in the construction of the model, but also structural variables in order to identify the characteristics of the farms that have the higher influence. Another objective is to be able to predict these variables at the farm level, using structural variables that are easy to measure. The data used in this work were obtained from a questionnaire survey to the holders/managers of a sample of 69 dehesa farms in Extremadura (SW Spain). The statistical methodology used for the construction of the model was Partial Least Square Regression (PLSR). It can be concluded that the variables relative to farm intensification, to labour and especially to Iberian pig breeding, are those that take part mainly in the model.
Keywords: Dehesa; gross output; Livestock farming systems; partial least square regression

Economic and management characterization of dehesa farms: implications for their sustainability - Gaspar, P; Mesías, F J; Escribano, M; Rodriguez de Ledesma, A; Pulido, F (Agroforestry Systems, 2007)
Dehesa agroforestry systems occupy around 6 million ha in the Iberian Peninsula. Their economic and environmental sustainability depends on the maintenance of the extensive livestock farms which created this typical ecosystem. This work analyzes dehesa farms in the Extremadura region (SW Spain) using technical and economic indicators of 69 randomly selected holdings. Principal component analysis (PCA) allowed us to establish a valid model explaining 65.8% of the variance. The two principal components having most weight were Iberian pig production (explaining 20% of the variance of the model), and which ruminant species were raised on the farm (15% of the variance). A cluster analysis distinguished ﬁve types of farms: sheep farms at high and low stocking rates, beef cattle farms, wooded farms with mixed livestock, and farms with a high level of cropping activity. The most proﬁtable farms were those with either high overall livestock density or a high level of Iberian pig production. While high stocking density has historically attracted high levels of subsidy, production of Iberian pigs was proﬁtable because of the high value of the product. In the light of CAP reform, Iberian pig production seems the most readily sustainable type of farming for the dehesa system.
Keywords: cluster analysis; Farm typology; Livestock farming systems; Principal component analysis; Rangeland management

Economic and management characterization of dehesa farms: implications for their sustainability - Gaspar, P.; Mesías, F. J.; Escribano, M.; Rodríguez de Ledesma, A.; Pulido, F. (Agroforestry Systems, 2007)
Dehesa agroforestry systems occupy around 6 million ha in the Iberian Peninsula. Their economic and environmental sustainability depends on the maintenance of the extensive livestock farms which created this typical ecosystem. This work analyzes dehesa farms in the Extremadura region (SW Spain) using technical and economic indicators of 69 randomly selected holdings. Principal component analysis (PCA) allowed us to establish a valid model explaining 65.8% of the variance. The two principal components having most weight were Iberian pig production (explaining 20% of the variance of the model), and which ruminant species were raised on the farm (15% of the variance). A cluster analysis distinguished ﬁve types of farms: sheep farms at high and low stocking rates, beef cattle farms, wooded farms with mixed livestock, and farms with a high level of cropping activity. The most proﬁtable farms were those with either high overall livestock density or a high level of Iberian pig production. While high stocking density has historically attracted high levels of subsidy, production of Iberian pigs was proﬁtable because of the high value of the product. In the light of CAP reform, Iberian pig production seems the most readily sustainable type of farming for the dehesa system.
Keywords: cluster analysis; Farm typology; Livestock farming systems; Principal component analysis; Rangeland management